Information als Schutzgegenstand - Zech, Herbert (Mohr Siebeck, 2020)
How is information protected by property rights? Information goods such as news, images, gene sequences or stored data can be classified as semantic, syntactic or structural information. Herbert Zech shows that information is allocated exclusively not only by intellectual property rights but also in other fields of law.